Re-accumulation of macular pigment after successful macular hole surgery. Issue 5 (2nd September 2015) - Bottoni, Ferdinando; Zanzottera, Emma; Carini, Elisa; Cereda, Matteo; Cigada, Mario; Staurenghi, Giovanni
Abstract : Aims: To investigate macular pigment optical density (MPOD) during follow-up of sealed macular holes and to study correlations of MPOD with progressive changes in spectral-domain optical coherence tomography (SD-OCT) and functional results. Methods: Consecutive patients (n=18) who had undergone successful vitrectomies for idiopathic macular holes were evaluated postoperatively at 1, 3, 6 and 9 months. At each follow-up visit, MPOD was measured with a modified confocal scanning laser ophthalmoscope and the outer retina evaluated by SD-OCT. The changes of MPOD postoperatively and the relationship of MPOD and SD-OCT findings to best corrected visual acuity were examined. Results: MPOD did not change significantly throughout follow-up, from 0.49±0.22 (mean±SD) at month 1 to 0.42±0.18 at month 9. There was a tendency towards a significant association between amount of MPOD and recovery of external limiting membrane during follow-up (p=0.068). Best corrected visual acuity increased significantly from 0.24±0.12 before surgery to 0.65±0.25 at month 9. Recovery of the ellipsoid zone determined most of visual acuity improvement (p=0.024). MPOD was not associated with visual acuity changes (p=0.394). Conclusions: Revisualisation of macular pigment after successful macular hole surgery is not associated with improved visual acuity and may merely be an accompanying sign of the reapposition of the edges of the hole.